2013
DOI: 10.1104/pp.112.212068
|View full text |Cite
|
Sign up to set email alerts
|

Iron Is Involved in the Maintenance of Circadian Period Length in Arabidopsis      

Abstract: The homeostasis of iron (Fe) in plants is strictly regulated to maintain an optimal level for plant growth and development but not cause oxidative stress. About 30% of arable land is considered Fe deficient because of calcareous soil that renders Fe unavailable to plants. Under Fe-deficient conditions, Arabidopsis (Arabidopsis thaliana) shows retarded growth, disordered chloroplast development, and delayed flowering time. In this study, we explored the possible connection between Fe availability and the circad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 65 publications
2
57
0
Order By: Relevance
“…Several studies have shown that the chlorophyll a transient has become one of the most popular tools to estimate stress-induced changes in photosynthetic performance. For example, the shape of the OJIP transient seems to be particularly sensitive to environmental stresses, such as drought [55], salt stress [56], high temperature [57], and heat stress [58]. The chlorophyll fluorescence parameter Fv/Fm has been used as an indicator of physiological stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the chlorophyll a transient has become one of the most popular tools to estimate stress-induced changes in photosynthetic performance. For example, the shape of the OJIP transient seems to be particularly sensitive to environmental stresses, such as drought [55], salt stress [56], high temperature [57], and heat stress [58]. The chlorophyll fluorescence parameter Fv/Fm has been used as an indicator of physiological stress.…”
Section: Discussionmentioning
confidence: 99%
“…Artificial night lighting significantly damaged the donor side of PSII, which was indicated by significant increase of the K step in the OJIP transients and the relative variable fluorescence at the K step ( Figure 2). Specifically, the peak of the K-step under stress is an effective injury indicator relative to the inactivation of the oxygen-evolving complex (OEC) to the donor side of PSII [32,57,60]. The dramatic inhibition of the O 2 evolution capacity of leaves exposed to artificial night lighting suggested that the donor side of PSII was damaged during artificial night lighting.…”
Section: Discussionmentioning
confidence: 99%
“…In 2013, three independent studies showed that Fe-deficiency slows down the pace of the core clock (Chen et al 2013;Hong et al 2013;Salomé et al 2013). Functional chloroplasts, but not photosynthetic activity, were shown to be necessary for the period lengthening induced by Fe deficiency (Chen et al 2013;Salomé et al 2013).…”
Section: Ironmentioning
confidence: 99%
“…These data indicate that gun mutant screens specifically disrupted a few distinct mechanisms that downregulate the expression of PhANGs when chloroplast biogenesis is blocked, not complex metabolic situations. The findings that these mechanisms appear conserved in all plants tested [17] and contribute to stress tolerance [4,5,11,14], the circadian rhythm [7,8] and development [38][39][40][41] provide evidence that they contribute plastid-to-nucleus signalling in natural environments.…”
Section: The Gun Mutant Screenmentioning
confidence: 99%
“…Extraplastidic signalling mechanisms, plastid-to-nucleus signalling mechanisms and the integration of these signalling mechanisms are major regulators of photosynthesis-associated nuclear genes (PhANGs) [1][2][3]. Plastidto-nucleus signalling affects numerous plastidic and extraplastidic processes, such as the biogenesis of chloroplasts and amyloplasts [3][4][5][6], the circadian rhythm [7,8], DNA replication [3], the transcription of genes that encode ribosomal RNA by RNA polymerase I [9], development [10] and the optimization of photosynthesis to various qualities of light [3]. Plastid-to-nucleus signalling also contributes to the response to wounding, biotic stress, abiotic stress and sugar [2,3,9,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%